Intelegensia Kalkulus : Integrasi AI dalam Pembelajaran Kalkulus - Kesumawati, Ayundyah (Universitas Islam Indonesia, 2025)
The purpose of this study was to examine the interaction between students and an Artificial Intelligence tutor, specifically through the use of ChatGPT in Calculus learning. The implementation of Artificial Intelligence (AI) in calculus learning has the potential to enhance students’ learning experiences both inside and outside the classroom. In this context, AI can be utilized to support better problem-solving skills and strengthen students’ understanding of fundamental mathematical concepts. The use of ChatGPT in learning was intended to maximize the knowledge transfer process beyond regular classroom hours. The learning process was conducted through the integration of AI as a virtual tutor in Integral Calculus courses. Students used AI collaboratively and independently to solve problems through structured prompts designed in accordance with the course learning outcomes. The evaluation was conducted qualitatively through observations and student satisfaction questionnaires, and quantitatively through the measurement of Course Learning Outcome (CPMK) achievement. Based on the observations and assessments, the findings indicate that the implementation of ChatGPT can effectively support the knowledge transfer process outside classroom sessions, with a course completion rate of 88%. Furthermore, sentiment analysis of student comments revealed that 50% of students expressed positive responses, and five main topics were identified from the comments related to the implementation of the learning process.